Adsorption of cationic dye textile wastewater using Clinoptilolite: isotherm and kinetic study. Issue 1 (2nd January 2019) - Molla Mahmoudi, Mohammad; Nadali, Azam; Soheil Arezoomand, Hamid Reza; Mahvi, Amir Hossein
Abstract: The releasing of dye-contained effluents has become an objectionable problem in these decades. Thus, the aim of the present work was to evaluate the potential of the acid-treated Clinoptilolite for Methylene Blue (MB) dye removal from aqueous solution. In this experimental-lab study, the dye adsorption onto acid-treated Clinoptilolite was carried out in batch adsorption system. Brunauer-Emmet-Teller (BET) analysis, Scanning Electron Microscopy (SEM), XRF analysis and X-ray diffraction (XRD) were utilized to characterize the acid-treated Clinoptilolite. The effect of some parameters on adsorption efficiency including pH, adsorbent dosage, initial dye concentration and contact time were studied. The isotherm and kinetic study were applied to describe the data obtained from the dye adsorption process. The results indicated that increasing the studied parameters had direct and positive effect on the dye adsorption efficiency. The results showed that higher dye adsorption efficiency was observed at pH=10, adsorbent dosage of 0.5 g/L, dye concentration of 50 mg/L and contact time of 90 min. the isotherm and kinetic studies are better described by pseudo-second kinetic model and Langmuir isotherm model. It can be concluded that acid-treated Clinoptilolite can be used as an effective adsorbent to remove the MB dye from aqueous solution.